Analysis of Calculation, Payment, and Reporting of PPh Article 21 at PT. X (Case Study 2020) - Sherly, Sherly; Safira, Safira (Jurnal Ilmu Ekonomi dan Sosial (JIES), 2024)
Many companies experienced significant revenue declines due to social restrictions and temporary business closures. This has impacted their ability to fulfill their tax obligations, including PPh Article 21. The research subject is PT. X, a company engaged in offset packaging printing. This study uses a qualitative method, addressing issues by collecting, describing, calculating, comparing, and explaining a situation. Specifically, this study is a descriptive research type. The results of the research show that PT. X's calculation of Income Tax Article 21 is still not in accordance with Tax Law No. 36 of 2008.